Фотолюмінесценція та оптичне поглинання монокристалів і скла тетраборату літія, легованого іонами срібла та мангану - Ignatovych, M. V. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2009)
Silver and manganese -doped lithium tetraborate single crystal and glassy phosphors with different dopant content were studied. Optical absorption, steady-state and time-resolved photoluminescence techniques were used. for spectral characterization of samples. Optical absorption- as well as photoluminescence excitation and emission spectra of LTB:Mn single crystal revealed that manganese is present only in the form of Mn2+ions, while in the glassy LTB:Mn simultaneous presence of Mn2+ and Mn3+ ions was detected. Optical absorption and photoluminescence spectral characterization of LTB:Ag single crystal showed that only one type of Ag1+ ions are absorbing and emitting centres while in the LTB:Ag glassy samples the presence of at least two non-equivalent surrounding of Ag1+ ions was revealed.